PENGARUH LABA PER LEMBAR SAHAM DAN NILAI PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Trustorini Handayani; Via Mutiara Sari (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2014)
ABSTRACTThis study was to determine the effect of Earning Per Share (EPS) and Price to Book Value (PBV) to Stock Price on Textile and Garment companies listed in Indonesia Stock Exchange, both together (simultaneously) or partially.The method is used in this research is descriptive method, verification with quantitative approach. The analytical method used is the method of multiple linear regression analysis. The analytical method used is the method of multiple linear regression analysis. Besides previously also classical assumptions which include normality test, test Multicollinearity, heteroskidastity test, and autocorrelation test. pearson correlation analysis, determination coefficient, and hypothesis test. The result showed that there were no irregularities clasical assumptions, it is shown that the available data has been qualified to use multiple linear regression models. The method of analysis used is multiple linear regression analysis with the help of analysis tools SPSS version 21.0The results of this study showed that partially Earning per Share (EPS) significantly affects stock price, and the variable Price To Book Value (PBV) not significant effect on stock price, simultaneously Earning per Share (EPS) and Price To Book Value (PBV) significantly affects stock price.Keywords : earning per share, price to book value, and stock price